Silver Nanoparticles at Biocompatible Dosage Synergistically Increases Bacterial Susceptibility to Antibiotics - Ipe, Deepak S.; Kumar, P. T. Sudheesh; Love, Robert M.; Hamlet, Stephen M. (Frontiers in Microbiology, 2020)
Antibiotics used to treat bacterial infections can become ineffective over time or result in the emergence of antibiotic resistant pathogens. With the advent of nanotechnology, silver nanoparticles (AgNPs) have gained significant attention as a therapeutic agent due to the well-known antimicrobial properties of silver. However, there are concerns and limited literature on the potential cytotoxicity of nanoparticles at effective antimicrobial concentrations. AgNPs prepared from silver nitrate with glucose reduction were characterized by surface plasmon resonance, dynamic light scattering, zeta potential analysis and transmission electron microscopy. The cytotoxicity of AgNPs towards human gingival fibroblasts over 7 days was determined using cell proliferation assays and confocal microscopy. AgNP MIC and antibacterial effects alone and in combination with 11 antibiotics were determined against a panel of nine microbial species including gram-positive and gram-negative bacterial species. AgNPs concentrations ≤ 1 μg/mL were non-cytotoxic but also showed no antibacterial effects. However, when combined with each of eleven antibiotics, the biocompatible concentration of AgNPs (1 μg/mL) resulted in significant inhibition of bacterial growth for multiple bacterial species that were resistant to either the antibiotics or AgNPs alone. This study presents a promising strategy with further testing in vivo, to develop novel antimicrobial agents and strategies to confront emerging antimicrobial resistance.